Did Anti-dumping Duties Really Restrict Import?: Empirical Evidence from the US, the EU, China, and India - Nakgyoon Choi (East Asian Economic Review (EAER), 2017)
This paper studied the effects of anti-dumping measures on the imports to investigate whether the trade restriction effect of an anti-dumping duty is dominant. Our results indicate that a 1% increase in the anti-dumping duties decreases the import of the targeted product by about 0.43~0.51%. The actual statistics, however, show that the total import of the targeted products increased by about 30 percent while an anti-dumping duty was in force. That indicates that an anti-dumping duty is just a temporary import relief. This paper also investigated whether an anti-dumping duty is terminated in the case that the injury would not be likely to continue or recur if the duty were removed. The hazards model estimates show that increase in market share, MFN tariff rate, and dumping margin decrease the hazard of termination of an anti-dumping duty, but the increase in value added increases the hazard of termination. Generally speaking, this result indicates that the WTO member countries have regulated the overuse of an anti-dumping measure. The findings of this paper show that there is a country- and industry-wise heterogeneous characteristic in the effect as well as termination of an anti-dumping duty.
Keywords: F10; F13; F14; 330; Anti-dumping Duty; Trade Restriction Effect; Termination Of An Anti-dumping Duty; Two-stage Model; Cox Proportional Hazards Model